ANALISIS PENGARUH CELEBRITY ENDORSER RACHEL VENNYA DI INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN PRODUK ERIGO DI KOTA PALEMBANG - Felicia Angela; Lina Lina (LPPM Universitas Multi Data Palembang, 2023)
This study aims to analyze the influence of celebrity endorser Rachel Vennya on Instagram on purchase decision for Erigo products in Palembang City. This study uses primary data. This research is a type of field study research with the method of collecting data with the survey method, with data collection techniques using purposive sampling technique with predetermined respondent criteria. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the celebrity endorser variable (trustworthiness, attractiveness, expertise) Rachel Vennya on Instagram has a positive and significant effect on purcahse decision for Erigo products in Palembang City. Keywords : Celebrity Endorser, Trustworthiness, Attractiveness, Expertise, Purchase Decision.